CLINICAL SIGNS AND PATHOMORPHOLOGICAL PICTURE OF HYPOXIC INTRAVENTRICULAR HEMORRHAGE IN NEWBORNS - L.V. Ledyaikina; L.A. Balykova; A.V. Gerasimenko; E.I. Naumenko (Вопросы современной педиатрии, 2009)
(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(2):124-125)